2010
DOI: 10.1017/s0022029910000579
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of bovine lactoferrin and citrate in milk during experimental endotoxin mastitis in early-versuslate-lactating dairy cows

Abstract: Lactoferrin (Lf) is a molecule naturally present in bovine milk that affects the availability and transport systems of iron. Lf also binds endotoxin (lipopolysaccharide, LPS) of Gram-negative bacteria and modulates the immunological response. In the present study, concentrations of bovine Lf (bLf) and citrate in milk were determined in early (EL) and late (LL) lactating dairy cows, using an experimentally induced endotoxin mastitis model and a crossover design. Nine clinically healthy Finnish Ayrshire cows wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…This chelated form of iron effectively reduces the iron availability in environments such as milk and insect hemolymph. Thus, citrate can be considered an iron sequestration factor that may prevent bacterial growth in these environments (47)(48)(49). The ferric dicitrate receptor FecA, along with its accessory proteins FecB and FecC, enables bacteria to transfer ferric dicitrate across the outer membrane and to incorporate essential iron (50,51).…”
Section: Resultsmentioning
confidence: 99%
“…This chelated form of iron effectively reduces the iron availability in environments such as milk and insect hemolymph. Thus, citrate can be considered an iron sequestration factor that may prevent bacterial growth in these environments (47)(48)(49). The ferric dicitrate receptor FecA, along with its accessory proteins FecB and FecC, enables bacteria to transfer ferric dicitrate across the outer membrane and to incorporate essential iron (50,51).…”
Section: Resultsmentioning
confidence: 99%
“…Concentration of citrate was greater by 36 h post-IMI challenge followed by a decrease in citrate to concentrations below those observed at h = -12 (Figure 5I) whereas citrate yield was lower by 24 h post-IMI challenge (Figure 5J). Concentration of milk citrate was also shown to decrease in LPS challenged quarters from lactating dairy cows [42]. Milk citrate, a marker of mitochondrial metabolism in the mammary gland [43], induces the ferric citrate transport system and is competing with lactoferrin for iron [42].…”
Section: Resultsmentioning
confidence: 99%
“…Concentration of milk citrate was also shown to decrease in LPS challenged quarters from lactating dairy cows [42]. Milk citrate, a marker of mitochondrial metabolism in the mammary gland [43], induces the ferric citrate transport system and is competing with lactoferrin for iron [42]. Lactoferrin contributes to host defense by binding iron thereby reducing availability of iron to invading bacteria [44] and lower yield of citrate may indicate an increase in the iron-binding capacity of bovine lactoferrin [45].…”
Section: Resultsmentioning
confidence: 99%
“…Regardless, milk citrate may be a more useful indicator of early signs of PI and off-feed situations rather than fat content due to (1) the greater %chg in milk citrate (44.7%) compared with fat content (35.3%) during restriction and (2) the low specificity of milk fat because it is has been shown to be positively associated with other common health disorders (Appuhamy et al, 2009;Moyes et al, 2009). Citrate, to our knowledge, has only been associated with mastitis, in which opposite patterns of change are observed when compared with PI; that is, decreases in milk citrate for cows with mastitis (Hyvönen et al, 2010). However, Sloth et al (2003) observed no difference in milk citrate between cows with healthy and experimentally infected quarters.…”
mentioning
confidence: 86%